GreCo: Green code of ethics. Issue 2 (31st January 2017) - Moraga, Ma Ángeles; García‐Rodríguez de Guzmán, Ignacio; Calero, Coral; Johann, Timo; Me, Gianantonio; Münzel, Harald; Kindelsberger, Julia
Abstract: Background: Codes of ethics (CoE) are widely adopted in several professional areas, including that of Software Engineering. However, contemporary CoE do not pay sufficient attention to one of the most important trends to have appeared in the last years environmental issues. Aim: The aim of this study is to establish a Green CoE for software engineering and Professional Practices (GreCo). Our intention is to cover a wide range of aspects related to sustainability, such as economic, environmental, social, and technical features. We are additionally interested in encouraging software engineers to adopt these aspects. Methods: The Green CoE presented is the result of the interaction of several experts in the area. A first version of GreCo, whose starting point was a discussion at the GInSEng workshop, was created by identifying key principles and adapting them to the Green area. Next, various important CoE were reviewed so as to gather the existing references to sustainability or to detect new ones. These elements would then possibly be incorporated into the new code or stimulate the creation of new sustainable principles. Results: The final result is the GreCo code, which has been produced by modifying existing principles or by the introduction of new ones.